Impact of foreign direct investment on carbon emission in Sub-Saharan Africa: The mediating and moderating roles of industrialization and trade openness - Joseph Owusu Amoah; Imhotep Paul Alagidede; Yakubu Awudu Sare (Cogent Business & Management, 2023)
Over the years, Sub-Saharan Africa (SSA) has become the pollution haven for most industrious companies around the globe due to foreign direct investment (FDI) activities. As a result, policymakers and researchers are striving to implement policies to guide the conduct of FDI since ineffective policies and strategies on FDI will increase carbon emissions in SSA. Also, integrating the mediating and moderating roles of industrialization and trade openness is yet to receive significant research attention in developing economies like SSA. Hence, this current study fills the gap in the literature and provides novel insight into FDI and carbon emissions. Taking into account the mediating and moderating roles of industrialization and trade openness. The study employed panel data comprising 30 countries in SSA from 2000 to 2022, which was used for the empirical investigation. The study utilized the common correlated effects mean group as the primary estimator and the augmented mean group as the robustness estimator. The findings affirm the need for the government in SSA to strengthen policies governing FDI to reduce carbon emission since FDI inflows positively affect carbon emission, while FDI outflows negatively affect carbon emission. Also, the mediating role results affirm the need for government restructuring policies governing industrialization to reduce carbon emissions in SSA. Lastly, the moderating findings demonstrate the need for effective policies on trade openness to reduce carbon emissions.
Keywords: 650; carbon emission; foreign direct investment; industrialization; Sub-Saharan Africa; urbanization and trade openness